2021
DOI: 10.1111/1365-2664.13913
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the camera trap methodologies used to estimate density of unmarked populations

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(112 citation statements)
references
References 48 publications
3
107
0
2
Order By: Relevance
“…It should be noted that despite the significant effect of the camera trap model, we did not find any association between theoretical trigger speed (ranging from 0.25 to 1.2, Table 1) and the probability of rapid activation. This can be explained as a consequence of the variability in intra-camera trigger times observed in other studies (https:// www.trailcampro.com/collections/trail-camera-reviews; Palencia, Rowcliffe et al, 2021), the type of detection zone (zonal or conical, Driessen et al, 2017), and the relatively wide intervals (width = 2.5 m) that have been considered here to evaluate the trigger speed. Future studies therefore should be designed to explore the relevance of the trigger speed by considering shorter intervals, and potentially, not only radials but also angled intervals (Howe et al, 2017;Rowcliffe et al, 2011).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It should be noted that despite the significant effect of the camera trap model, we did not find any association between theoretical trigger speed (ranging from 0.25 to 1.2, Table 1) and the probability of rapid activation. This can be explained as a consequence of the variability in intra-camera trigger times observed in other studies (https:// www.trailcampro.com/collections/trail-camera-reviews; Palencia, Rowcliffe et al, 2021), the type of detection zone (zonal or conical, Driessen et al, 2017), and the relatively wide intervals (width = 2.5 m) that have been considered here to evaluate the trigger speed. Future studies therefore should be designed to explore the relevance of the trigger speed by considering shorter intervals, and potentially, not only radials but also angled intervals (Howe et al, 2017;Rowcliffe et al, 2011).…”
Section: Discussionmentioning
confidence: 92%
“…a common detection zone for the 15 camera traps at each sampling point) and were later used to locate the position of the individuals registered. We considered 10 m as maximum distance based on previous studies that reported detection distances for the species sampled in this study (Hofmeester et al, 2017;Palencia, Rowcliffe et al, 2021). The cameras were angled to be parallel to the slope of the ground.…”
Section: Experimental Designmentioning
confidence: 99%
“…The REST model requires some assumptions, including the certain detection of animals entering the focal area (Nakashima et al 2018); however, it is an efficient and realistic method for estimating the density of ground‐dwelling mammals lacking individually recognizable markings (Palencia et al 2021). In the model, the relationship between animal density D and camera trap data is described by the following equation: D=E(Y)×E(T)/(sHa)…”
Section: Methodsmentioning
confidence: 99%
“…For example, nocturnal distance sampling with thermal imagers (Franzetti et al 2012, Focardi et al 2020) and capture-mark-recapture with ear tags (Hebeisen et al 2008) or DNA (Ebert et al 2012) are used to estimate the absolute density of wild boar. Recently, methods for the estimation of the absolute density of mammals from camera trap data without individual identification have been devised and used, such as the random encounter model (REM; Rowcliffe et al 2008), spatially explicit N-mixture model (Chandler and Royle 2013), distance sampling (CTDS; Howe et al 2017), and random encounter and staying time model (REST; Nakashima et al 2018), and some of these have been applied to wild boar (Palencia et al 2021). However, methods for estimating absolute density are often not suitable for monitoring over large spatial areas (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, time series of WVC data could be used for monitoring population trends in a multi season framework. In this context, abundance predictions from the Royle–Nichols models should be evaluated to study their ability to be extrapolated, down or upscaled, etc., using other independent sources such as telemetry or camera trapping studies (Palencia et al 2021).…”
Section: Concluding Remarks and Recommendationsmentioning
confidence: 99%